Temporal association of maternal weight gain with early-term and preterm birth and low birth weight babies - Jan Mohamed, Hamid Jan; Lim, Poh Ying; Loy, See Ling; Chang, Kah Haw; Abdullah, Ahmad Fahmi Lim (Wolters Kluwer, 2021)
Background: Low birth weight and preterm or early-term babies may have a higher risk of poor health. One of the main factors is the weight gain of a pregnant woman during gestational weeks in the second and third trimesters. Changes in weight over a month in a pregnant woman might also have an impact on infant outcomes. This study aimed to investigate the association between maternal weight at different time points and low birth weight and preterm or early-term babies (premature babies). Methods: A total of 156 pregnant women were recruited. Maternal weight was collected at different gestational weeks. Maternal age, body mass index, delivery mode, delivery week, and infant weight were also recorded. Maternal data were restructured into a person-period format before mixed-effects multiple logistic regression was used. Various weight variables with either a fixed effect or time-varying effects were tested in the model. Results: Thirty (19.23%) women had delivered low birth weight or premature babies. Multiple logistic regression model demonstrated that mothers with higher increases in weight at 32 weeks of gestation than that in the predelivery stage had a lower probability of having a low birth weight or premature baby (odds ratio [OR] = 0.64; 95% CI, 0.49-0.85; p < 0.001). Women with a weight increase of more than 2 kg in a 4-week gestation period had a higher probability of having a low birth weight or premature baby than those with an increment of <1 kg (OR = 8.43; 95% CI, 2.90-24.54; p < 0.001). Conclusion: An increase in weight gain after 32 weeks was shown to reduce the risk of low birth weight and premature babies. Maternal weight monitoring was suggested to be conducted every 4 weeks to minimize the chance of having a low birth weight and premature baby.